The effect of small leaks, grain bulk, and the patching of leaks on the performance of hermetic storage. (May 2015) - Martin, D.T.; Williams, S.B.; Baributsa, D.; Murdock, L.L.
Abstract: Hermetic storage containers are often used by farmers to protect their harvested grain from insect damage and ultimately stop insect population development. Sometimes holes in a storage container are created by insects or by accident; such holes may reduce the effectiveness of the hermetic storage unit. Using cowpea grain and the cowpea bruchid, Callosobruchus maculatus (F), we investigated the degree to which holes in a hermetic storage container wall affect the level of grain damage. When there were low numbers of holes, seed damage increased markedly with each additional hole. The grain itself contributed a barrier to oxygen diffusion through the grain mass. If holes in the container wall were patched with a single layer of HDPE film, grain damage was indistinguishable from that seen under full hermetic conditions. We provide evidence that a single layer of woven polypropylene contributes a small but measurable barrier to oxygen penetration into the container. Highlights: Holes in hermetic containers allow insects and damage to develop only in nearby grain. The distance oxygen diffuses limits the distance insects and damage can occur. One factor limiting oxygen availability is the grain itself. Patching holes prevents insects from developing. The woven polypropylene outer PICS bags contributes slightly to the hermetic effect.